Reflow soldering : apparatus and heat transfer processes - Illes, Balazs; Krammer, Oliver; Geczy, Attila (Elsevier, 2020)
Reflow Soldering: Apparatus and Heat Transfer Processes investigates the technology of reflow soldering from the aspect of the soldering ovens and apparatus. The authors begin by introducing the concept of surface mount technology. This is followed by three chapters exploring: Infrared ovens, convection ovens, Vapor Phase Soldering (VPS), and special reflow ovens. Each of these chapters includes a discussion of the physical background, structure and working principle, and characterization of the heating, flow and vapor parameters; and concludes with a review of the application of the techniques and typical solder failures. The book concludes with a discussion of the various numerical simulations of the different ovens. This book will be useful for researchers and process and quality and research and design engineers within the electronics and manufacturing industries. Provides an overview and comparison of the existing reflow apparatus, heating methods, and working principlesAnalyses and compares the different reflow ovensDiscusses useful tools such as characterization and measurement methods and includes numerical case studies to assist in solving soldering problems and improve soldering qualityIntroduces Vapor Phase Soldering (VPS) technology